1980
DOI: 10.1007/bf01886619
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Mooren's ulcer in Nigeria

Abstract: Five cases of Mooren's ulcer in young Nigerians seen over a 2-year period, in Lagos, healed after limbal conjunctivectomy. The maximum follow up in 2 cases was 2 years. Previous trauma or corneal foreign bodies as seen in four of our cases seem to suggest the precipitation of Mooren's ulcer by various ocular insults. We believe that collagenolytic activity of the conjunctiva plays a prominent role in the pathogenesis of the ulcer and is supported by this report in which our five cases healed after excision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…[30,31] It is a type of peripheral ulcer usually associated with autoimmune disease or immunological reactions to mycobacterial and Staphylococcus aureus toxins. The present study recorded eight eyes with Mooren's ulcer in seven male and one female patients.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] It is a type of peripheral ulcer usually associated with autoimmune disease or immunological reactions to mycobacterial and Staphylococcus aureus toxins. The present study recorded eight eyes with Mooren's ulcer in seven male and one female patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Since the earliest descriptions of Mooren's ulcer, [7][8][9][10] much of what is known of the demographics, history and clinical presentation of this condition has been gleaned from a relatively limited number of small case series and isolated case reports. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Liberal interpretation of these studies has given rise to widely held concepts regarding age, gender and race as predictors of severity and laterality, views that have been questioned in light of the varied composition and small size of these reported cohorts. 30 31 We present here the demographic, historical and clinical characteristics of a large cohort of patients with Mooren's ulcer seen at Aravind Eye Hospital, Madurai, Tamil Nadu, India.…”
mentioning
confidence: 99%
“…1 Additional reports from Africa have confirmed an association of Mooren's ulcer with helminthic infection. 2,3 Kuriakose suggested that the ulcer is the result of corneal response to a toxin secreted by microfilariae. 1 We suggest that there is an autoimmune response in the cornea triggered by the host's response to a nematode antigen that cross-reacts with a specific corneal protein.…”
Section: Discussionmentioning
confidence: 99%